Halting the destruction of the rain forests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
workshop was held on the management and development of the tropical rainforest ecosystem on 12-16 March in Cayenne, Guyana